A student-led course in clinical reasoning in the core curriculum - Zijdenbos, Ingeborg L. (IJME, 2010)
OBJECTIVES: There is growing evidence for the value of several forms of peer teaching in medical education. Little is known about the feasibility of such an approach in courses of clinical reasoning. The University Medical Center Utrecht offers a clinical reasoning course for first and second year students which previously had been occasionally led by sixth year, i.e. near-peer students. We evaluated a version of this course, fully delivered by final year students. METHODS: In 2008-2009 this highly structured mandatory clinical reasoning course for second year medical students was fully tutored by final year medical students, as part of a teacher training course in their core curriculum. Routine evaluations before and after introducing near-peers as tutors were compared, a focused questionnaire survey was conducted, as well as an interview with a group of students to evaluate the new format. RESULTS: There was no difference in the ratings of the course before and after the introduction of the new format. In general, second year students are satisfied with the near-peer teachers. Strong points mentioned are their high motivation, involvement, enthusiasm, adjustment of cognitive level of teaching to the recipient students and stimulating skills. CONCLUSIONS: Although our study cannot provide evidence for differential learning effects, the evaluation of our final year student led clinical reasoning course shows encouraging results.